Flomoxef and fosfomycin in combination for the treatment of neonatal sepsis in the setting of highly prevalent antimicrobial resistance. (15th February 2022) - Darlow, Christopher A.; Farrington, Nicola; Johnson, Adam; McEntee, Laura; Unsworth, Jennifer; Jimenez-Valverde, Ana; Kolamunnage-Dona, Ruwanthi; Da Costa, Renata M A; Ellis, Sally; Franceschi, François; Sharland, Mike; Neely, Michael; et al.
Abstract: Background: Neonatal sepsis is a serious bacterial infection of neonates, globally killing up to 680 000 babies annually. It is frequently complicated by antimicrobial resistance, particularly in low- and middle-income country (LMIC) settings with widespread resistance to the WHO's recommended empirical regimen of ampicillin and gentamicin. Objectives: We assessed the utility of flomoxef and fosfomycin as a potential alternative empirical regimen for neonatal sepsis in these settings. Methods: We studied the combination in a 16-arm dose-ranged hollow-fibre infection model (HFIM) experiment and chequerboard assays. We further assessed the combination using clinically relevant regimens in the HFIM with six Enterobacterales strains with a range of flomoxef/fosfomycin MICs. Results: Pharmacokinetic/pharmacodynamic modelling of the HFIM experimental output, along with data from chequerboard assays, indicated synergy of this regimen in terms of bacterial killing and prevention of emergence of fosfomycin resistance. Flomoxef monotherapy was sufficient to kill 3/3 strains with flomoxef MICs ≤0.5 mg/L to sterility. Three of three strains with flomoxef MICs ≥8 mg/L were not killed by fosfomycin or flomoxef monotherapy; 2/3 of these were killed with the combination of the two agents. Conclusions: These data suggest that flomoxef/fosfomycin could be an efficacious and synergistic regimen for the empirical treatment of neonatal sepsis in LMIC settings with prevalent antimicrobial resistance. Our HFIM results warrant further assessment of the flomoxef/fosfomycin combination in clinical trials.